2012
DOI: 10.1007/s11121-012-0297-y
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Relationship Security as a Moderator of Home Visiting Impacts on Maternal Psychosocial Functioning

Abstract: There is variability in home visiting program impacts on the outcomes achieved by high risk families. An understanding of how effects vary among families is important for refining service targeting and content. The current study assessed whether and how maternal attributes, including relationship security, moderate short- and long-term home visiting impacts on maternal psychosocial functioning. In this multisite RCT of home visiting in a population-based, ethnically-diverse sample of families at risk for maltr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 32 publications
1
12
0
1
Order By: Relevance
“…It is also possible to compare the results of the current study with those of our randomized trial of home visiting impacts on maternal psychosocial functioning in Hawaii (McFarlane et al 2013). As in the current study, we used the Attachment Style Questionnaire to measure maternal relationship anxiety and discomfort with trust.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…It is also possible to compare the results of the current study with those of our randomized trial of home visiting impacts on maternal psychosocial functioning in Hawaii (McFarlane et al 2013). As in the current study, we used the Attachment Style Questionnaire to measure maternal relationship anxiety and discomfort with trust.…”
Section: Discussionmentioning
confidence: 99%
“…For example, research has shown positive program impacts on maternal sensitivity to infant cues for mothers who endorsed depressive symptoms (Spieker et al 2005). Research has also shown that relationship insecurity moderates program impacts (McFarlane et al 2013). For example, mothers with high relationship anxiety but not avoidance showed the greatest benefits in psychosocial functioning (McFarlane et al 2013).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cette évaluation a mis en lumière la nécessité de documenter de manière flexible et évolutive les changements qui s'opèrent au sein des familles et qui ne sont pas toujours perceptibles dans le contexte d'une visite ponctuelle effectuée dans le cadre d'un projet de recherche. Ce constat est partagé par plusieurs études qui soulignent la difficulté de démontrer les effets positifs associés aux programmes en négligence (MacMillan et al, 2009;McFarlane et al, 2012).…”
Section: La Négligence Auprès Des Enfants Est Un Phénomène Reconnu Etunclassified